Protein‐protein interaction networks as miners of biological discovery. Issue 15 (24th May 2022) - Wang, Steven; Wu, Runxin; Lu, Jiaqi; Jiang, Yijia; Huang, Tao; Cai, Yu‐Dong
Abstract: Protein‐protein interactions (PPIs) form the basis of a myriad of biological pathways and mechanism, such as the formation of protein complexes or the components of signaling cascades. Here, we reviewed experimental methods for identifying PPI pairs, including yeast two‐hybrid (Y2H), mass spectrometry (MS), co‐localization, and co‐immunoprecipitation. Furthermore, a range of computational methods leveraging biochemical properties, evolution history, protein structures and more have enabled identification of additional PPIs. Given the wealth of known PPIs, we reviewed important network methods to construct and analyze networks of PPIs. These methods aid biological discovery through identifying hub genes and dynamic changes in the network, and have been thoroughly applied in various fields of biological research. Lastly, we discussed the challenges and future direction of research utilizing the power of PPI networks.